An Examination of the Chinese Banking System: Scale Economies, Cost Efficiency, Profitability and Financial Stability Modelling - Hou, Jiakun (2022)
This thesis is a timely and warranted examination of the scale and performance of the Chinese banking system for the years 2005 to 2015. Firstly, in light of the policy debate over “too big to fail”, we examine evidence on the scale economies of banks, as well as technological change, to inspect whether industry consolidation is a rational objective for the larger banks in China to continue their asset growth. Secondly, utilising Stochastic Frontier Analysis, we construct a stochastic frontier cost function to examine the evolution of cost efficiency in the banking sector. Thirdly, considering the intense restructuring of banks over the study observation period, we explore the underlying variables that explain the profitability of Chinese banks. Finally, the driving factors that affect the resilience of Chinese banks are evaluated with the aim of maintaining the financial stability of the banking system.